Time management disposition and relevant factors among new nurses in Chinese tertiary hospitals: A cross-sectional study - Xie, Jianfei; Wu, Xiaoqi; Li, Jie; Li, Xiaolian; Xiao, Panpan; Wang, Sha; Zhong, Zhuqing; Ding, Siqing; Yan, Jin; Li, Lijun; Cheng, Andy S. K. (Frontiers in Psychology, 2022)
Introduction New nurses struggled with time management, which was a prominent theme in safety care for patients. However, the transition training of time management for new nurses was complicated and ignored by clinical managers. The purpose of this study was to understand the level of new nurses’ TMD from a nationwide perspective and detect the influencing factors of the TMD. Materials and methods A cross-sectional study design with a stratified sampling method was sampled in China. Six hundred and seventy new nurses within the first year of employment were recruited. New nurses’ time management disposition, job stressors, self-efficacy, clinical communication competence, and safety behavior were measured by corresponding scales. Results New nurses showed the best sense of time’s value, followed by the sense of time efficacy and time monitoring view for time management disposition. The related factors of time management disposition were communication skills, safety behavior, job stressors, and being without a preceptor. New nurses’ time management disposition was at a moderate level and they performed worse in time allocation. The highest education, with or without a preceptor, the experience of part-time jobs, and class cadre were significantly influencing the time management disposition of new nurses. Conclusion Nursing managers should pay attention to new nurses’ time management disposition. Reducing the job stressors, improving communication ability, and safe behavior were important measures to improve the time management disposition.